A Connection Cloud Model Coupled With Improved Conflict Evidence Fusion Method for Prediction of Rockburst Intensity - Guangyao Chen (IEEE Access, 2021)
As a common geological hazard in underground engineering, rockburst has many uncertain factors and interactions, and is of a complicated mechanism. Based on the information fusion theory, a methodology using a novel connection cloud model, which can overcome the defect of the traditional cloud model requiring factors to be normal distribution when determining the basic probability assignment function of the evidence is proposed for predicting the rockburst intensity. And concepts of Lance-distance and Deng-entropy are also introduced here to improve the traditional evidence fusion algorithm. The practical application shows that the result obtained from the proposed model is consistent with that in the actual site testing, so this model is feasible and effective for the prediction of the rockburst intensity. Furthermore, compared with results from other six improved evidence fusion rules, the improved evidence fusion method proposed here has higher fusion convergence precision, faster convergence rate, and more accurate and reliable results, this may provide a new reference for other similar uncertain problems.